2016
DOI: 10.1007/s10578-016-0656-1
|View full text |Cite
|
Sign up to set email alerts
|

Empathic Responses to Mother’s Emotions Predict Internalizing Problems in Children of Depressed Mothers

Abstract: Recent theories posit that empathy, typically an adaptive characteristic, may be associated with internalizing problems when children are chronically exposed to mother’s depression. We tested this postulation in a sample of children (N=82, Mage=5 years). Children witnessed their mothers express sadness, anger, and happiness during a simulated phone conversation, and researchers rated children’s negative affective empathy, positive affective empathy, and information-seeking (cognitive empathy) in response to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 69 publications
5
19
1
Order By: Relevance
“…The protective effect of sensitive parenting is suggested in a longitudinal study where maternal sensitivity was found to decrease the risk for internalizing problems in adolescence [57]. Research has indicated [18,54] the exposure to mother's depressed emotions as a mechanism through which the risk for internalizing problems is transmitted.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of sensitive parenting is suggested in a longitudinal study where maternal sensitivity was found to decrease the risk for internalizing problems in adolescence [57]. Research has indicated [18,54] the exposure to mother's depressed emotions as a mechanism through which the risk for internalizing problems is transmitted.…”
Section: Discussionmentioning
confidence: 99%
“…8 Maternal depression elicits symptoms such as withdrawal, irritability, and melancholy, which may disturb how sensitive and positively engaged the mother is with her child. 9-11 Mothers with depressed symptoms are less involved with their children and have difficulty expressing positive reactions to their child leading to more negativity and less interaction, touch, and vocalization. 7,12 These mothers are more likely to ignore their child, becoming disengaged and flat, causing them to “gaze less at their infants, rock their infants less,” 13 provide minimal comfort in response to their children’s distress, and even utilize “denial as a discipline strategy.” 14…”
Section: Impact Of Maternal Depression On Parenting Behaviorsmentioning
confidence: 99%
“…10 Children tend to internalize a depressed mother’s sadness and irritability, resulting in lower utilization of facial emotion communication, negative reactivity to stressful situations, and a failure to acquire and practice complex emotion regulation strategies. 9,11,34,36 One study by Feng et al 9 found that when children of depressed mothers were presented with a disappointing experience, the mothers tended to be less positive and their children exhibited a more negative mood and lower levels of active emotion regulation. Studies have also shown that a depressed mother’s tendency to neglect a child’s needs and provide less expression stimulation contributes to a greater difficulty in differentiating emotional faces.…”
Section: Impact Of Maternal Depression On Childrenmentioning
confidence: 99%
“…This capacity is essential for successfully navigating daily social life, given its role as the “social glue” in stimulating social belongingness (De Waal, 2009 ). Higher levels of empathy are associated with better social competence and fewer symptoms of internalizing and externalizing problems (e.g., Mayberry & Espelage, 2007 ; Pursell et al, 2008 ; Smith, 2015 ; Tully & Donohue, 2017 ). Yet despite its importance in children’s psychosocial wellbeing, very little is known about the development of such capacity in children with a cochlear implant (CI), who are at risk for experiencing difficulties in social participation during early childhood as a result of hearing loss (Bat-Chava & Deignan, 2001 ; Calderon & Greenberg, 2012 ; Punch & Hyde, 2011 ; Rieffe et al, 2015 ).…”
mentioning
confidence: 99%
“…A longitudinal account of empathy is highly relevant to our knowledge of social-emotional development, as empathy is consistently found to play a protective role in typical development. For example, a higher level of empathy is associated with fewer internalizing symptoms, such as depression and anxiety (e.g., Smith, 2015 ; Tully & Donohue, 2017 ), and with fewer externalizing behaviors, such as aggression and conduct problems (e.g., Mayberry & Espelage, 2007 ; Pursell et al, 2008 ). According to two longitudinal studies in typically developing preschool children, this negative association between empathy (measured as an overall response) and behavioral difficulties is stable from preschool to early primary school years (Hastings et al, 2000 ; Zhou et al, 2002 ), suggesting that empathy is effective in reducing behavioral problems.…”
mentioning
confidence: 99%